2021
DOI: 10.1016/j.ihj.2021.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery diameter – A correlation between intravascular ultrasound and quantitative coronary angiography

Abstract: Coronary angiography mostly underestimates coronary artery size. Indian data is scarce on correlating quantitative angiographic coronary diameter (D QCA ) to intravascular ultrasound derived coronary diameter (D IVUS ). We retrospectively analyzed 10-year data (2008–2017) of patients undergoing IVUS guided left main percutaneous coronary intervention (LM-PCI). LM, ostio-proximal LAD (op-LAD), and ostio-proximal LCX (op-LCX) were analyzed in 186, 177 and 44 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…A comparison of our study with other studies is shown in Table 2. The diameter of the left main vessel was similar to the findings of Goel et al 7 who used IVUS to determine left main diameter in an Indian population. However, ours is the first study to have used OPTICROSS 6 (40 MHz) and OPTICROSS HD (60 MHz), which we believe to be superior technologies as compared to previous-generation IVUS and hence give a better understanding of the left main segment.…”
Section: Discussionsupporting
confidence: 85%
“…A comparison of our study with other studies is shown in Table 2. The diameter of the left main vessel was similar to the findings of Goel et al 7 who used IVUS to determine left main diameter in an Indian population. However, ours is the first study to have used OPTICROSS 6 (40 MHz) and OPTICROSS HD (60 MHz), which we believe to be superior technologies as compared to previous-generation IVUS and hence give a better understanding of the left main segment.…”
Section: Discussionsupporting
confidence: 85%
“…This may be explained by the improper sizing of the stent at proximal segments depending only on angiographic assessment. Vessel under sizing when using angiographic assessment has been recently reported in a recent study done by Goel et al, [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To choose the diameter range of coronary arteries according to the classification of studies presented in Table A1 of References 37–44 in Appendix A, a diameter of 3 mm was chosen for this research.…”
Section: Methodsmentioning
confidence: 99%